Respostas

2014-05-14T21:30:40-03:00
Primeira:
y²-7y+6=0
delta= (-7)²-4.1.6
delta=49-24
delta=25
Y=7+/- raiz de 25 (tudo isso, sobre 2)
Y=7+/-5 ( Sobre 2)
Y'=12 (Sobre 2)
Y'= 6
Y''= 2 (Sobre 2)
Y''= 1
Solução= {1,6}

Segunda:
16x²+8x+1=0
delta= 8²-4.16.1
delta= 64-64
delta=0
X= -8 (Sobre 32)
X= -1 (Sobre 4)
Solução= {-1(Sobre4)}
2014-05-14T21:49:46-03:00
Em Y² - 7y + 6= 0, temos:
Delta = (-7)² - 4.1.6 --> 49 - 24 --> Delta =25 --> Raiz² de Delta = 5, logo temos:
-(-7) +/-  5 : 2 --> 7 + 5: 2 = 12:2= 6 --> Primeira raiz.
----------------------> 7 - 5: 2= 2:2= 1-------> Segunda raiz.    R: (1 e 6)

Em 16x² + 8x + 1 =0, temos:
Delta = (8)² - 4.16.1--> 64 - 64 --> Delta = 0. Quando Delta = 0, só há uma raiz. Logo temos: -8 : 2 x 16 = -8 : 32.      R: (-8:32)